Определение возраста волка (Canis lupus L.) по черепу - Гурский, И.Г. (Вестник зоологии, 1973)
Age peculiarities of the wolf skull are described: development and change of teeth, size and shape of processes and crests, obliteration of sutures, degree of teeth wearing depending on the form of bite. The key for determination of wolf age by the skull is given.